2018
DOI: 10.3390/ijerph15081693
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Psychosocial Pathways of Parks’ Effects on Health: A Qualitative Study

Abstract: Urban green space has been positively associated with psychological and physical health. However, the linkage between exposure to parks and health outcomes remains unclear. The current study examined the meanings that people assign to city parks, as a way to understand the pathways by which parks exert their effects on health. We conducted qualitative interviews with twenty culturally diverse residents in New York City. Thematic analysis was performed on the qualitative data. Results showed that all themes ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…While we discuss findings focused on urban settings, additional research on social cohesion in suburban and rural settings can also be explored. This insight also supports the need to incorporate psychosocial factors in strategies in planning [105] and health promotion. We believe that our discussion on green spaces, social cohesion, and social capital will advance transdisciplinary research and inform programmatic strategies to promote nature-based health promotion.…”
Section: Next Steps and Future Researchsupporting
confidence: 54%
See 2 more Smart Citations
“…While we discuss findings focused on urban settings, additional research on social cohesion in suburban and rural settings can also be explored. This insight also supports the need to incorporate psychosocial factors in strategies in planning [105] and health promotion. We believe that our discussion on green spaces, social cohesion, and social capital will advance transdisciplinary research and inform programmatic strategies to promote nature-based health promotion.…”
Section: Next Steps and Future Researchsupporting
confidence: 54%
“…As a sense of belonging involves feelings of acceptance and inclusion in social groups, it is also considered another mechanism between social ties and improved physical and psychological health [100,104]. For example, some perceive city parks as a way to connect with and strengthen ties with loved ones, neighbors, nature, and their community [105]. Thus, urban green spaces can potentially promote social cohesion through feelings of comfort, which connect people to particular places and with the people who visit them [24].…”
Section: Potential Mechanisms and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Being connected with others is an important aspect of human health and wellbeing [ 45 , 46 ] that is, the two themes presented within “Enticing” are interlinked concepts. Previous studies have similarly shown that urban parks provide opportunities for people to connect with others in the natural environment [ 47 ], and people who spend time in a natural environment are more likely to report good health and wellbeing [ 48 ]. White et al [ 48 ] self-report survey study with 19,806 people reported those who were outside in nature for between 120–180 min in the previous week were more likely to report good health (OR = 1.59 [95% CI: 1.31–1.92]) and high wellbeing (OR= 1.23 [95% CI: 1.08–1.40]) than those who had no contact with the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is considered that the detailed exploration of concepts and causal relations is beyond the scope of this study. Given that relationships are important to human beings as they provide beneficial effects on health and well-being (Swierad and Huang, 2018), the main implication of the results is that the expansion of green welfare, which incorporates psychological factors, is important. Specifically, the results revealed the awareness of participants regarding various relationships, and also confirmed that the relationship formation through 1) connectedness with self, 2) connectedness with neighbors, and 3) connectedness with nature, had effects on reduction in psychological and physical risk factors associated with dementia by alleviating feelings of isolation and enhancing a sense of well being, thus helping them acquire healthy lifestyle habits.…”
Section: Improvement Of Health-related Lifestylementioning
confidence: 99%